MICRO-CREDIT AND EMPOWERMENT : A STUDY OF KUDUMBASHREE PROJECTS INKERALA, INDIA - V P Raghavan (Journal of Rural Development, Vol. 28, No. (4), pp. 469 - 484, 2009)
Poverty alleviation schemes based on micro- credit system have been implemented in many of the developing countries in recent years. The Government of Kerala State in India has introduced a novel scheme of poverty alleviation based on micro-credit and self-help grouping. Paraphrased as Kudumbashree ( `Prosperity of the Family'), the scheme aims at improving the living levels of the poor women in rural and urban areas. It seeks to bring the poor women folk together to form the grassroot organisations to help enhance their economic security. The project aims at removing poverty among ruralwomen households through setting up of micro-credit and productive enterprises. The activities such as micro-credit and micro-enterprises under the scheme were undertakenby the locally formed Community Development Societies comprising poor women. The State Poverty Eradication Mission-Kudumbashree- launched by the Government of Kerala in India is a massive poverty eradication programme in contemporary history. It has proved without doubt that women empowerment is the best strategy for poverty eradication. Women, who were regarded as voiceless and powerless started identifyingtheir inner strength, opportunities for growth, and their role in reshaping their own destiny. The process of empowerment becomes the beacon light to their children, theirfamilies and the society at large. It opens a new vistas in development history. A new paradigm of participatory economics has been found emerging in "God's Own Country".Kudumbashree presents a unique model of participatory development , which can very well , be emulated by other developing countries.